THE PRACTICALITY OF INTERACTIVE MULTIMEDIA SOFTWARE LECTORA INSPIRE TOWARDS LEARNING THEME 3 OF GRADE IV ELEMENTARY SCHOOL STUDENTS - Mike Oktavia; Yanti Fitria (Jurnal Cakrawala Pendas, 2023)
The use of technology in the classroom today is still uneven because of teachers who prefer to use traditional media, such as the images found in student textbooks, rather than technology-assisted media. This leads to students becoming bored with their lessons, which results in less effective learning. In grade IV of an elementary school. The ADDIE methodology was applied in this research to generate interactive multimedia.Using the following methods: analysis, planning, development, application, and assessment. Response questionnaires, specifically those from students and teachers, are used to collect data. this study seeks to ascertain the usefulness of interactive multimedia development assisted by Lectora Inspire software. The research of the grade IV teachers at SDN 11 Tanjung Barulak's practicality test results showed that 91.66% of them met the requirements for being "extremely practical," and the examination of the student replies to the questionnaire showed that 89.94% of them did as well.As for the practicality of the class IV teacher response at SDN 02 Tanjung Barulak, 87.50% was included in the "very practical" criteria, and as for the practicality of the class IV student response at SDN 14 Tanjung Barulak, 96.38% was included in the "very practical" criteria, and as for the practicality of the class IV teacher response at SDN 02 Tanjung Barulak, 87.50% was included in the "very practical" criteria.and while the questionnaire for the practicality of student responses was 90.55% of the "very practical" criteria. By describing the effectiveness of interactive multimedia helped by lectora inspire software, a descriptive data analysis technique was utilized to analyze the data. The achieved practicality value reveals itself in extremely practical criteria, indicating that the interactive multimedia can be useful and make learning more convenient. Pada zaman sekarang ini dengan memanfaatkan teknologi dalam proses pembelajaran masih belum merata yang disebabkan oleh guru yang cenderung menggunakan media konvensional berupa media gambar yang terdapat dalam buku paket siswa dan masih kurang menggunakan media berbantuan teknologi dalam pembelajaran yang menyebabkan siswa merasa bosan dalam kegiatan proses belajar sehingga pembelajaran menjadi kurang maksimal. Penelitian ini bertujuan untuk mengetahui nilai kepraktisan dari pengembangan multimedia interaktif berbantuan software lectora inspire yang diimplementasikan di kelas IV SD. Dalam penelitian ini model yang digunakan adalah model ADDIE. Dengan langkah yaitu, analisis, perencanaan, pengembangan, penerapan, dan evaluasi. Pengumpulan data menggunakan angket respon yaitu respon siswa dan guru. Teknik analisis data yang digunakan ialah teknik analisis data deskriptif yaitu dengan mendeskripsikan kepraktisan multimedia interaktif  berbantuan software lectora inspire. Hasil analisis yang mendapatkan hasil uji kepraktisan guru Kelas IV SDN 11 Tanjung Barulak yang menunjukkan 91,66% dengan kriteria “sangat praktis”, dan angket kepraktisan respon dari siswa menunjukkan 89,94% dimana termasuk dengan kriteria “sangat praktis”. Sedangkan untuk respon guru Kelas IV SDN 14 Tanjung Barulak menunjukkan 93,66% dengan kategori “sangat praktis”, dan untuk angket kepraktisan siswa menunjukkann 96,38% yang termasuk kedalam kriteria “sangat praktis”, dan untuk kepraktisan dari respon guru Kelas IV SDN 02 Tanjung Barulak yaitu 87,50% termasuk ke dalam kriteria “sangat praktis”, dan sedangkan angket kepraktisan respon siswa yaitu 90,55%  kriteria “sangat praktis”. Nilai kepraktisan yang diperoleh menunjukkan dalam kriteria sangat praktis yang diartikan bahwa  multimedia interaktif  yang dikembangkan dapat memberikan kemudahan dan membantu dalam penggunaanya dalam proses pembelajaran.